Cultura organizacional y comportamiento innovador en la Cooperativa de Ahorro y Crédito “Occidental” - Ordoñez Loza, Brithney Noelia (2024)
Over the last few years, savings and credit cooperatives have sought a different vision from Organizational Culture (OC), which involves Innovative Behavior (IC), that allows to guarantee success and growth within the financial environment. Therefore, this study allows promoting the innovations generation, what help to strengthen the CO of the Cooperative, providing benefits and opportunities for innovative behavior growth, in these circumstances, the current investigative work aim was to determine the relationship between the organizational culture and innovative behavior within a savings and credit cooperative; for this, it was made first a bibliographic research about the variables. The research had a quantitative approach with a descriptive and correlational scope, for this, it was applied a developed instrument by Shirali, with respect to organizational culture, and for Lukes and Stephen innovative behavior, considering the Western Savings and Credit Cooperative by taking into account the 88 collaborators from the 11 agencies nationwide, getting a sample 79 collaborators. The got results with respect to organizational culture mark that 60.36% employees have a neutral assessment from organizational culture their institution, while regarding innovative behavior 69.63% employees agree. Furthermore, the results show, what there is a moderate positive correlation 0.455 between the considered variables. In conclusion, the organizational culture from the cooperative affects the innovative behavior same and vice versa.